Strengthening Public Service Ethics in Government: The South Korean Experience. (14th November 2017) - Suk Kim, Pan; Yun, Taebeom
Abstract : Among the various laws in South Korea, the most important for strengthening public service ethics in the government include the following three major acts: the Public Service Ethics Act, the Anti-Corruption Act, and the Improper Solicitation and Graft Act. The main goal common to the three acts is the prevention of conflicts of interest (COI). Appropriately managing issues related to COI is the shortest route to bolstering public service ethics and preventing corruption. Focusing on these three acts, this article discusses what efforts have been made in Korea to strengthen public service ethics and prevent corruption. The article discusses such efforts to ensure that government officers remain ethical in relation to three stages: taking up public office before employment, holding office, and after leaving office. It also reviews the backgrounds to and processes of enacting the three acts and explores their major issues and shortcomings.